Jacek Kaczmarski i Gert Hofmann przed Ślepcami Pietera Bruegla - Gajak-Toczek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article indicates intellectual connections between a painting by a Dutch master (The Blind), a poem by a Polish bard (The Parable of the Blind) and a novel by a German writer (Blindensturz). The painting by the sixteenth century painter inspired 20th century creators to reflect on the surrounding world, the purpose and the meaning of human life which fate is ruled by hubris, pride, hate, and the want of dominance over others. Despite the immense power of evil – in the opinion of the writers – it is vital to attempt again and again to aim at cultivating the elements which constitute the good side of human nature which imparts human dimension to our existence. Through falling down, tripping, experiencing pain and suffering the blind rise and overcome personal and physical constraints. They let us believe that such deeds can be performed by anyone.